Evaluation of TRPA1 as a Therapeutic Target in MYCN-Amplified Neuroblastoma - Seger, Alexandra ; 0000-0003-3191-5302; Adamič, Dora ; 0009-0003-5487-5590; Olmos, Erick Muciño ; 0000-0001-5018-247X; Nilsson, Johannes; Granados-Aparici, Sofia; Vieco-Marti, Isaac; Esfandyari, Javanshir; Engström, Matilda; Martinez, Julia ; 0009-0004-4050-8439; Mañas, Adriana; Navarro, Samuel; Noguera, Rosa; et al. (Pediatric Blood & Cancer, 2025)
BACKGROUND: Neuroblastoma (NB) is a childhood cancer with a high relapse rate despite intensive treatment. TRPA1 is a pain-sensing ion channel with downstream impacts on proliferative and pro-apoptotic pathways. Here, we evaluated TRPA1 expression in NB and performed pharmacological inhibition in preclinical models to assess its potential as a therapeutic target in NB. METHODS: TRPA1 protein levels were assessed in NB patient tumors on tissue microarrays. Bulk and single-cell gene expression data were retrieved from publicly available databases. The effects of three TRPA1 inhibitors (AP-18, A967079, and Bay 390) on NB cell viability and cell death were evaluated using NB patient-derived xenograft (PDX)-derived organoids. In vivo testing was performed in a MYCN-amplified NB PDX model. Drug combination testing was performed using combination or sequential treatments and evaluated using drug synergy scores. RESULTS: TRPA1 is widely expressed in NB patient tumors and preclinical patient-derived NB models. Pharmacological TRPA1 inhibition decreased NB cell viability and increased cell death. In vivo TRPA1 inhibition alone did not significantly affect NB tumor growth. Pretreatment with TRPA1 inhibition prior to chemotherapy resulted in synergistic effects in vitro. CONCLUSIONS: TRPA1 is expressed in NB tumors, and pharmacological TRPA1 inhibition can be effective in vitro and synergistic when used as pretreatment to chemotherapy. However, the tested inhibitors did not show in vivo efficacy, at least as monotherapy.
© 2025 The Author(s). Pediatric Blood & Cancer published by Wiley Periodicals LLC.
Keywords: Neuroblastoma/drug therapy; Humans; TRPA1 Cation Channel/antagonists & inhibitors; Animals; N-Myc Proto-Oncogene Protein/genetics; Mice; Xenograft Model Antitumor Assays; Gene Amplification; Tumor Cells, Cultured; Cell Proliferation; Mice, SCID; Mice, Inbred NOD; chemotherapy; neuroblastoma; TRPA1